2019
DOI: 10.3390/en12244653
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gas–Liquid Flow Characteristics in Geometrically Different Swirl Generating Devices

Abstract: The gas–liquid flow characteristics for blade, single, and the double-helical swirl elements were numerically investigated and compared in this work. The Euler–Euler model assuming bi-modal bubble size distributions was used. The experiment, conducted in a vertical pipe equipped with a static blade swirl element, was used as the basis for the computational fluid dynamics (CFD) simulations. In the experiment, high-resolution gamma-ray computed tomography (HireCT) was used to measure the gas volume fractions at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Rotating flow can be found in nature, such as ocean whirlpool [1], tropical cyclones and tornadoes [2] as well as in many engineering applications such as heat transfer [3], combustion [4], phase separation and mixing [5], [6]. In the case of gas-liquid flow, a static swirl element can be used inside a pipe to generate the rotating flow responsible either for mixing or separating the gas and liquid phases [6], [7]. In contrast to a single-phase flow, the gas-liquid flow inside a static mixer is a complex phenomenon [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotating flow can be found in nature, such as ocean whirlpool [1], tropical cyclones and tornadoes [2] as well as in many engineering applications such as heat transfer [3], combustion [4], phase separation and mixing [5], [6]. In the case of gas-liquid flow, a static swirl element can be used inside a pipe to generate the rotating flow responsible either for mixing or separating the gas and liquid phases [6], [7]. In contrast to a single-phase flow, the gas-liquid flow inside a static mixer is a complex phenomenon [8].…”
Section: Introductionmentioning
confidence: 99%
“…The computational fluid dynamics (CFD) simulations using the Euler-Euler approach based on the experiment of [6] and [8] were performed by [9] and [8], respectively. A numerical study to compare the gas-liquid flow characteristics for a different type of static swirl elements (i.e., the blade type, the single helix, and the double helix swirl elements) using CFD was performed by [7]. A numerical investigation by [10] demonstrated that the gas distribution inside the vertical static mixer is also influenced by the length to diameter ratio of the static swirl.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the flow resistance increases as well [4]. Therefore, many researchers investigated and optimized the hydrodynamic and mixing performance of static mixers with helical flow channels in recent years [10]. Lei et al [11] numerically studied the fluid flow and heat transfer of pipe flow in a modified helical static mixer with perforated holes on the staggered twisted tapes (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Swirl elements with different geometries can be found in the open literature e.g. [9]. Figure 1 shows a double helical swirl element [9] used in our preliminary experiment at the Laboratory of Fluid Mechanics, Department of Mechanical and Industrial Engineering, Universitas Gadjah Mada.…”
Section: Introductionmentioning
confidence: 99%
“…[9]. Figure 1 shows a double helical swirl element [9] used in our preliminary experiment at the Laboratory of Fluid Mechanics, Department of Mechanical and Industrial Engineering, Universitas Gadjah Mada. The element was placed in a vertical pipe to generate swirling flow for the separation between gas and liquid.…”
Section: Introductionmentioning
confidence: 99%